The Puzzle of Transparency Reforms in the Council of the EU - Naurin, Daniel (2017)
I argue that the transparency reforms that have been implemented in the Council of the EU in the last decades are unlikely to change the perception of the Council as a non-transparent institution. My argument is based on three distinctions: the distinction between transparency (availability of information) and publicity (spread and reception of information); between transparency in process and transparency in rationale; and between plenary and committee decision-making arenas in legislatures. While national parliaments tend to have all these features, the Council of the EU only has two (transparency in process and committee decision-making). As a consequence, publishing ever more documents and detailed minutes of committee meetings is unlikely to strengthen the descriptive legitimacy of the Council. Furthermore, I argue that the democratic transparency problem is the reverse of what is most often argued: It is not the lack of transparency that causes a democratic deficit, but the (perceived) lack of a democratic infrastructure that makes more serious transparency reforms unthinkable to government representatives.